Synthesis of Hydroxyapatite thin films on PMMA Printed Substrates - Sauñi Camposano, Yesenia Haydee (Pontificia Universidad Católica del Perú, 2018)
Each year millions of people suffer from bone defects resulting from trauma, tumors or bone-related injuries. Therefore there is a need to continuously develop new materials or improve the properties of the materials currently used, for bone replacement or implant applications. Polymethyl methacrylate (PMMA) has proven to be a promising alternative as a material for implants; however, there are still some limitations inherent to this material, particularly related to its surface properties. This thesis work is focused on the fabrication of hydroxyapatite (HAp) thin films on the surface of 3D printed PMMA substrates. 3D printing, particularly the Fused Deposition Modeling (FDM) technique was used to fabricate PMMA substrates with different surface porosity levels. FDM technique exhibits the potential for fabricating customized freeform structures for several applications including craniofacial reconstruction. HAp thin films were deposited by Radio Frequency Magnetron Sputtering (RFMS) and Ion Beam Sputtering (IBS) techniques, with a commercial target and an “in house” sintered target, respectively. A structural, chemical, mechanical, and morphological characterization was conducted in the generated surfaces by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and hardness and roughness measurements. The results of the XRD analysis revealed an amorphous structure for the films produced by both RFMS and IBS techniques on the PMMA substrates. The micrographs obtained by SEM showed a columnar morphology and a low density for the films produced by RFMS; the same technique revealed a structure of ridges of standing platelets with curved contours for the IBS deposited films. The amorphous structure and the morphology of the films, as well as the hardness and roughness can be propitious to improve surface properties and promote the osseointegration capabilities of PMMA. This work contributes to the basis for the development of a PMMA implant manufacturing process using 3D printing and HAp film deposition techniques, with improved osseointegration properties.

Cada año, millones de personas sufren defectos óseos como resultado de traumas, tumores o lesiones relacionadas con los huesos. Por lo tanto, existe la necesidad de desarrollar continuamente nuevos materiales o mejorar las propiedades de los materiales utilizados actualmente, para aplicaciones de reemplazo óseo o implantes. El polimetilmetacrilato (PMMA) ha demostrado ser una alternativa prometedora como material para implantes; sin embargo, todavía existen algunas limitaciones inherentes a este material, particularmente relacionadas con sus propiedades superficiales. Este trabajo de tesis se centra en la fabricación de películas delgadas de hidroxiapatita (HAp) en la superficie de sustratos de PMMA impresos en 3D. La impresión 3D, particularmente la técnica de modelado de deposición fundida (FDM), se utilizó para fabricar sustratos de PMMA con diferentes niveles de porosidad superficial. La técnica FDM exhibe el potencial para fabricar estructuras personalizadas de para varias aplicaciones, incluida la reconstrucción craneofacial. Las películas delgadas de HAp se depositaron mediante técnicas de deposición catódica con Magnetrón y radio frecuencia (RFMS) y deposición catódica con haz de iones (IBS), con un target comercial y un target sinterizado "in house", respectivamente. Se realizó una caracterización estructural, química, mecánica y morfológica en las superficies generadas por medio de difracción de rayos X (XRD), microscopía electrónica de barrido (SEM), espectroscopía de energía dispersiva (EDS) y medidas de dureza y rugosidad. Los resultados del análisis de XRD revelaron una estructura amorfa para las películas producidas por ambas técnicas RFMS e IBS en los sustratos de PMMA. Las micrografías obtenidas por SEM mostraron una morfología columnar y una baja densidad para las películas producidas por RFMS; la misma técnica reveló una estructura de crestas de plaquetas con contornos curvados para las películas depositadas IBS. La estructura amorfa y la morfología de las películas, así como la dureza y la rugosidad pueden ser propicias para mejorar las propiedades de la superficie y promover las capacidades de oseointegración del PMMA. Este trabajo contribuye a la base para el desarrollo de un proceso de fabricación de implantes de PMMA usando impresión 3D y técnicas de deposición de película HAp, con propiedades mejoradas de oseointegración.
Keywords: Hidrocarburos policíclicos aromáticos; Películas delgadas; Implantes artificiales; https://purl.org/pe-repo/ocde/ford#2.05.01